Effects of shallow and deep endotracheal tube suctioning on cardiovascular indices in patients in intensive care units - Irajpour, Alireza (Medknow Publications & Media Pvt Ltd, 2014)
BACKGROUND: Clearing the endotracheal tube through suctioning should be done to promote oxygenation. Depth of suctioning is one of the variables in this regard. In shallow suctioning method, the catheter passes to the tip of the endotracheal tube, and in deep suctioning method, it passes beyond the tip into the trachea or brunches. This study aimed to evaluate the effect of shallow and deep suctioning methods on cardiovascular indices in patients hospitalized in the intensive care units (ICUs). MATERIALS AND METHODS: In this clinical trial, 74 patients were selected among those who had undergone mechanical ventilation in the ICU of Al-Zahra Hospital, Isfahan, Iran using convenience sampling method. The subjects were randomly allocated to shallow and deep suctioning groups. Heart rate (HR) and blood pressure (BP) were measured immediately before and 1, 2, and 3 min after each suctioning. Number of times of suctioning was also noted in both the groups. Data were analyzed using repeated measures analysis of variance (ANOVA), Chi-square and independent t-tests. RESULTS: HR and BP were significantly increased after suctioning in both the groups (P < 0.05). But these changes were not significant between the two groups (P > 0.05). The suctioning count was significantly higher in the shallow suctioning group than in the deep suctioning group. CONCLUSIONS: Shallow and deep suctioning were similar in their effects on HR and BP, but shallow suctioning caused further manipulation of patient's trachea than deep suctioning method. Therefore, in order to prevent complications, nurses are recommended to perform the endotracheal tube suctioning by the deep method.